Veiculação de derivado tiazolilhidrazona com atividade antifúngica em sistema nanométrico para melhoria da biodisponibilidade oral em modelo murino. - Iara Rinco Silva (2024)
The 2-[2-(cyclohexylmethylene)hydrazinyl]-4-phenylthiazole (RN104) exhibits significant antifungal activity against Cryptococcus species and low toxicity. However, its high lipophilicity (log P = 5.84) and poor aqueous solubility at physiological pH limit its oral bioavailability. To address these limitations, nanotechnology was employed through the development of self-emulsifying drug delivery systems (SEDDS) and nanostructured lipid carriers (NLC) for RN104 delivery. An HPLC-DAD analytical method was developed and validated for the quantification of RN104 in the formulations. Solubility studies in various excipients were conducted to design effective SEDDS and NLCs. Among the formulations, SEDDS demonstrated superior drug-loading capacity (10 mg/mL), stability (60 days), and ease of preparation and scale-up compared to NLC (1.5 mg/mL; 45 days). Optimization of the SEDDS-RN104 formulation using central composite design-response surface methodology (CCD-RSM) resulted in a particle size of 118.4 ± 0.7 nm and an encapsulation efficiency of 99.4 ± 0.1%. The SEDDS-RN104 formulation containing ascorbyl palmitate (0.1% w/w) as antioxidant was stable at room temperature for 6 months. In a pharmacokinetic study performed in mice, SEDDS-RN104 administered per os lead to a 21-fold increase in AUC0-t of RN104, compared to free drug. In vivo, SEDDS-RN104 showed enhanced antifungal efficacy in C57BL/6 mice (n = 6), with a survival curve superior to other treatments. These findings may be related to the improved pharmacokinetic parameters, including increased T½, reduced clearance, and significantly elevated Cmax. These results demonstrate that the incorporation of RN104 into SEDDS overcomes its pharmacokinetic limitations, leading to a substantial enhancement in therapeutic efficacy, being a promising alternative to the treatment of fungal infections.